Suppression of phase transitions and glass phase signatures in mixed cation halide perovskites - Mantas Simenas (Nature Portfolio, 2020)
Understanding the underlying physics and improving the performance of mixed lead halide perovskite materials remains a challenge. Here, the authors present experimental and theoretical study of structural phases, phase transitions, and dipolar dynamics in the mixed cation MA1-xDMAxPbBr3 perovskites.